Analysis of Insulin Resistance (HOMA-IR) with Urinary Albumin-Creatinine Ratio (uACR) in Non-Diabetic (DM) Subjects - Wali Syafaat, Andi; Nurahmi; Kurniawan, Liong Boy (Indonesian Association of Clinical Pathologist and Medical laboratory, 2025)
Insulin resistance (IR) is a conduit ion characterized by reduced sensitivity of peripheral tissues to the effects of insulin, resulting in a decrease in insulin's ability to stimulate glucose utilization in the body. This condition is not only found in obese subjects with diabetes mellitus (DM) but also in non-DM obese subjects. Kidney damage causes albuminuria, measured by calculating the albumin-to-creatinine ratio (uACR). IR is considered a strong predictor for determining the risk of albuminuria. The relationship between IR and uACR in non-DM adults has not been further studied. This study aims to analyze the relationship between HOMA-IR and uACR in non DM adults. This is a cross-sectional study using a sample of 90 non-DM adult subjects aged 20-40 years. Insulin levels in the blood and uACR were measured using the ECLIA method. Data were analyzed using SPSS version 25.No association was found between HOMA-IR and uACR in non-DM adult subjects (r = -0.55, p = 0.608). Furthermore, HOMA-IR had no relationship with uACR when classified by gender, age, or obesity status in non-DM adult subjects. There was no association between HOMA-IR and uACR in non-DM adult subjects.